The adenoid in children : a comparison of two methods of performing adenoidectomy and two methods of preparing the nose prior to endoscopy to assess adenoidal size - Jonas, N E (Division of Otorhinolaryngology, 2014)
Includes bibliographical references (leaves 49-50).